Productivity growth and the Phillips curve: a reassessment of the US experience - Marika Karanassou; Héctor Sala (Institute for the Study of Labor (IZA), 2009)
In this paper we analyse a new Phillips curve (NPC) model and demonstrate that (i) frictional growth, i.e. the interplay of wage-staggering and money growth, generates a nonvertical NPC in the long-run, and (ii) the Phillips curve (PC) shifts with productivity growth. On this basis we estimate a dynamic system of macrolabour equations to evaluate the slope of the PC and explain the evolution of inflation and unemployment in the US from 1970 to 2006. Since our empirical methodology relies heavily on impulse response functions, it represents a synthesis of the traditional structural modelling and (structural) vector autoregressions (VARs). We find that the PC is downward-sloping with a slope of -3.58 in the long-run. Furthermore, during the stagflating 70s, the productivity slowdown contributed substantially to the increases in both unemployment and inflation, while the monetary expansion was quite ineffective and led mainly to higher inflation. Finally, the monetary expansion and productivity speedup of the roaring 90s were both responsible for the significant lowering of the unemployment rate.
urn:nbn:de:101:1-2009082574
Keywords: E24; E31; 330; New Phillips curve; frictional growth; productivity growth; stagflating seventies; roaring nineties; impulse response functions; New-Keynesian Phillips Curve; Produktivität; Wirtschaftswachstum; Schätzung; USA